AUTOINSTRUIREA – BAZA PIRAMIDEI FORMĂRII PROFESIONALE CONTINUE - OSOIANU, Vera (BIBLIOPOLIS, 2020)
This article is about the importance of continuous learning at work place and of the auto learning in order to update the knowledges, skills and abilities in digital age. The author highlights the role of the information and communication technologies and especially of Web 2.0 applications, the opportunities offered for them in continuous learning of the librarians.